PENTINGNYA REVITALISASI MODAL SOSIAL PASKA PANDEMI COVID-19 - Max Regus (Research Centre for Population, Indonesian Institute of Sciences, 2020)
The COVID-19 pandemic brings many crucial issues that had never been imagined before, and even the following situation could not be predicted comprehensively. The world, on a large scale, and every country and community must ensure that they can get through this situation. This article explicitly wants to analyze how the community and other actors deal with this pandemic situation based on social capital. This article focuses on social capital in a pandemic defined by the emergence of voluntary networks between communities. Social capital has become one of the strengths of people in many places in facing the spread of COVID-19. Learning from COVID-19, this article argues that revitalizing social capital is one of the strategic pathways in dealing with a pandemic situation.